PENGARUH KESADARAN PAJAK, PENGETAHUAN PAJAK, SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR (STUDI KASUS KANTOR BERSAMA SAMSAT SURABAYA SELATAN) - Tituk Diah Widajantie; Dyah Ratnawati; Tamadoy Thamrin; Muhammad Hilmi Arifin (Behavioral Accounting Journal, 2019)
The tax is a compulsory levy paid by the citizen to the country and is used for the benefit of government and the general public. Tax is one of the country revenues to carry out the government activities, both the central and regional governments. A vehicle tax is a source of regional revenues. A compliance with vehicle taxpayers is one of the indicators in increasing local revenue. This research aimed to analyze the effect of taxpayer awareness, tax knowledge, and tax sanctions on vehicle taxpayer compliance. The population that has been used was all vehicle taxpayers in SAMSAT, South Surabaya. Meanwhile, the sample that has been used was 100 vehicle taxpayers by using random sampling technique. In this research, the data used a questionnaire. The technique of data analysis was using multiple linear analysis. The type of this research was quantitative research. The results of the research were the tax awareness and the tax sanctions significantly influenced vehicle taxpayer compliance while the tax knowledge had no effect on vehicle taxpayer compliance.